(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper expects to give a review of the substance andoutline of the online English newspapers in India. Twelve online Englishnewspapers published day by day in India were chosen for the study.The study utilized website content dissection to survey the substance andoutline of these newspapers. A checklist was created as the primary apparatusfor data accumulation and Microsoft Excel was utilized as the instrument fordata dissection. The study indicates that online English newspapers in Indiahave a normal example of substance, coverage, and plan. Substance accessibilityand access to the substance are the most common alternatives in these newspapers.Larger part of the newspapers utilization Blog, RSS and Facebook to associatewith their followers.